2022
DOI: 10.1021/acs.joc.1c02673
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Aryldiazophosphonates via a Diazo Transfer Reaction

Abstract: The simple synthetic procedure for preparation of α-aryl-α-diazophosphonates via a diazo transfer reaction is proposed. Benzylphosphonates reacted with tosyl azide (TsN3) in the presence of potassium tert-butoxide (KO t Bu) to afford diazophosphonates in a yield up to 79%. The proposed method is general. The reaction uses easily available starting materials, tolerates various functional groups, and may be applied for multi-gram scale synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Scheme 2 Summary of results on the synthesis of pyrazolines 1 and 5arylpyrazole-3-carboxylates 2 via 1,3-dipolar cycloaddition reaction of diazo compounds with dipolarophiles Recently we have reported an efficient approach to the synthesis of -aryl--diazophosphonates via diazo transfer reaction. 9 The method uses easily available starting materials (benzylphosphonates and TsN3) and a simple basic reagent (KO t Bu) and tolerates various functional groups giving target diazophosphonates in in a yield up to 79% (usually 55-70%). Three synthetic methodologies were elaborated for different types of aryl moiety in starting benzylphosphonate: 1) bearing electron-withdrawing groups; 2) bearing electron-donating groups; 3) and nitro group containing phosphonates.…”
Section: Figure 1 Pharmaceuticals Containing Pyrazole Ring Moietymentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme 2 Summary of results on the synthesis of pyrazolines 1 and 5arylpyrazole-3-carboxylates 2 via 1,3-dipolar cycloaddition reaction of diazo compounds with dipolarophiles Recently we have reported an efficient approach to the synthesis of -aryl--diazophosphonates via diazo transfer reaction. 9 The method uses easily available starting materials (benzylphosphonates and TsN3) and a simple basic reagent (KO t Bu) and tolerates various functional groups giving target diazophosphonates in in a yield up to 79% (usually 55-70%). Three synthetic methodologies were elaborated for different types of aryl moiety in starting benzylphosphonate: 1) bearing electron-withdrawing groups; 2) bearing electron-donating groups; 3) and nitro group containing phosphonates.…”
Section: Figure 1 Pharmaceuticals Containing Pyrazole Ring Moietymentioning
confidence: 99%
“…This compound is known. 9 Dimethyl 1-(3,4,5-trimethoxyphenyl)-1-diazomethylphosphonate (3v). Prepared according to general procedure C from dimethyl (3,4,5trimethoxybenzyl)phosphonate; yellow-orange oil (202 mg, 80% yield).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
See 1 more Smart Citation
“…In line with this notion, such diazo derivatives found no applications in synthesis until very recently, when it was shown that they can be generated and processed in flow at low temperature [45] . It is also important to note that the electrocyclic ring opening is not suppressed by imparting a donor/acceptor character onto a furfurylidene of type B , as the corresponding ester (R=COOEt) or phosphonate derivatives (R=P(O)(OR) 2 ) succumb to the very same process with similar ease [43,46,47] . Even attempts to intercept such intermediates by carrying out the diazo decomposition in neat styrene or cyclooctane resulted in very low yields [42] .…”
Section: Figurementioning
confidence: 99%
“…[45] It is also important to note that the electrocyclic ring opening is not suppressed by imparting a donor/acceptor character onto a furfurylidene of type B, as the corresponding ester (R=COOEt) or phosphonate derivatives (R=P(O)(OR) 2 ) succumb to the very same process with similar ease. [43,46,47] Even attempts to intercept such intermediates by carrying out the diazo decomposition in neat styrene or cyclooctane resulted in very low yields. [42] Along the same lines, an attempted copper-mediated reaction of A (R=H, X=NO 2 ) with neat cyclohexene failed to afford any cyclopropane or CÀ H insertion product.…”
mentioning
confidence: 99%